Which precedes? competition or cooperation? - Shamsudin, Norazidah; Hassan, Arif (Management Centre, IIUM, 2010)
This case study illustrates the issues related to team dynamics and why some teams fail to perform. It is the story of a motivated and competent marketing executive working in a bank, who excelled in her job until she was assigned to work in a team with two other persons. Initially the team worked well. However, when one member of the team was assigned some independent responsibilities from the branch manager of the bank, signs of team disintegration emerged and competition rather than cooperation dictated the relationship. This case provides lessons on behavioural issues while working in a team, the need for careful selection of team members, adequate support from the top management to the team, and some common management mistakes that create problems in team work.